Pengaruh Kompetensi, Etos Kerja dan Kedisiplinan Terhadap Kinerja Pegawai pada Kantor Sekretariat DPRD Provinsi Sumatera Selatan - Roni, Mukran; Rifqi, Muhamad Arry Naufal (CV. ITTC INDONESIA, 2024)
This research was conducted to examine employee performance within the Secretariat of the Regional People's Representative Council (DPRD) of South Sumatra Province, with the objective of assessing the influence of competency, work ethic, and discipline variables on employee performance. Employing a quantitative research method, the study targeted employees of the DPRD Secretariat, using purposive sampling to select 75 respondents. Both primary and secondary data were utilized, and data analysis included tests such as data quality assessment, classical assumption tests, statistical tests, and multiple linear regression analysis. The findings revealed that the competency variable (X1) significantly impacts employee performance, with a significance level of 0.001, less than 0.05, and a T-value greater than the T-table value (5.114 > 1.997). Similarly, the work ethic variable (X2) significantly affects performance, with a significance level of 0.001 and a T-value greater than the T-table value (6.045 > 1.997), while the discipline variable (X3) also has a significant effect, with a significance level of 0.015 and a T-value greater than the T-table value (2.490 > 1.997). Furthermore, the F-test results show that the F-calculated value (24.620) exceeds the F-table value (2.51), indicating that competency, work ethic, and discipline collectively have a positive and significant influence on employee performance in the Secretariat of DPRD South Sumatra Province